2017
DOI: 10.1021/acs.biochem.7b01025
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic Acid Metabolism by Human Cardiovascular CYP2J2 Is Modulated by Doxorubicin

Abstract: Doxorubicin (DOX) is a chemotherapeutic that is used in the treatment of a wide variety of cancers. However, it causes cardiotoxicity partly due to the formation of reactive oxygen species (ROS). CYP2J2 is a human cytochrome P450 that is highly expressed in cardiomyocytes. It converts arachidonic acid (AA) into four different regioisomers of epoxyeicosatrienoic acids (EETs). Using kinetic analyses we show that AA metabolism by CYP2J2 is modulated by DOX. We show that cytochrome P450 reductase (CPR), the redox … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 63 publications
(140 reference statements)
0
28
0
Order By: Relevance
“…The MD simulations support that up to three overlapping binding sites are possible, which can help to explain the observed complex AEA and eVD interactions, such as the regioselectivity change in the AEA metabolites ( Figure S29) and the potentiation of eVD metabolism (Figures 3 and 4). We have previously observed complex inhibition and regioselectivity changes for endogenous substrates of CYP2J2 59,96,97 ; however, this is the first report of a potentiation of CYP2J2 metabolism. Due to the poor solubility of the lipid substrates used in these studies, we could not accurately determine the binding constants to understand the cooperative nature of the potentiation.…”
Section: Levels Of Evds In Porcine Brain and Metabolism Of Exogenous mentioning
confidence: 59%
See 1 more Smart Citation
“…The MD simulations support that up to three overlapping binding sites are possible, which can help to explain the observed complex AEA and eVD interactions, such as the regioselectivity change in the AEA metabolites ( Figure S29) and the potentiation of eVD metabolism (Figures 3 and 4). We have previously observed complex inhibition and regioselectivity changes for endogenous substrates of CYP2J2 59,96,97 ; however, this is the first report of a potentiation of CYP2J2 metabolism. Due to the poor solubility of the lipid substrates used in these studies, we could not accurately determine the binding constants to understand the cooperative nature of the potentiation.…”
Section: Levels Of Evds In Porcine Brain and Metabolism Of Exogenous mentioning
confidence: 59%
“…In order to characterize the molecular basis of the multi-site kinetics observed with the eVDs, we performed MD simulations starting from membrane-bound structures of CYP2J2 in complex with substrates (AEA, NADA or NA5HT). Initial molecular docking was performed with AEA and either NADA or NA5HT in a stepwise manner 97 . These models allowed us to probe the binding mode of a second molecule to CYP2J2 in the presence of another molecule bound in the active site in an unbiased manner (i.e., without any assumptions about location of peripheral binding pockets).…”
Section: Molecular Dynamics (Md) Simulations Demonstrate Aea Stabilizmentioning
confidence: 99%
“…It is known that the major metabolite of DOX, doxorubicinol (DOXol), contributes to toxicity in the myocardium; however, other evidence suggests other metabolites of DOX, including DOX deoxyaglycone and DOXol hydroxyaglycone, may also contribute to the cardiotoxicity (Licata et al, 2000). In addition, P450 reductase can metabolize DOX to 7-deoxydoxyrubicin aglycone, which has been shown to inhibit AA metabolism, reducing the production of EETs and altering the regiosomers of EETs produced (Arnold et al, 2017). Therefore, increased metabolism through CYP2J2 may have a conflicting effect on the heart, elevating levels of toxic metabolites for certain drugs but increasing protection through EETs.…”
Section: Cardiac Hypertrophymentioning
confidence: 99%
“…4 In order to show this, we used an LC-MS/MS method to quantify the four regioisomers of EETs produced by CYP2J2 and its redox partner cytochrome P450 reductase (CPR). We found that DOX potently inhibits AA metabolism by CYP2J2 (Figure 1).…”
mentioning
confidence: 99%
“…2, 5 This is the first study demonstrating that a ligand binding directly at the active site of CYP2J2 alters the site of AA metabolism. 4 …”
mentioning
confidence: 99%